Aturan Hukum Terhadap Hak Cipta Video Youtube yang Diunggah Secara Ilegal - Istiawati, Sri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Youtube users who want to utilize it as a business medium, there are some rules to follow. The regulations set by Youtube also adjust according to the applicable laws of the country, where copyright is regulated. This is in line with the rise of Youtube channels that upload videos from their original channels without the permission of the video owner. With the rampant incident then the purpose of making this article is the protection of Copyright of Youtube content that is illegally uploaded (reuploaded) as well as an attempt to obtain Copyright protection in the work of Youtube content. The research method used is normative jurisprudence by analyzing legally based on material derived from RegulationsLegislationand literary materials related to Copyright. Through the results of the article drawn a conclusion that the moral right in the article UUHC states to still include or not include his name on the relevant copy of his work used for social, use an alias or real name, change, maintain the title, modify it. The filing of a litigation suit may be made to the Commercial Court with reference to Article 95 paragraph (2) UUHC. As well as potentially through non-litigation routes.